1977
DOI: 10.2136/sssaj1977.03615995004100040029x
|View full text |Cite
|
Sign up to set email alerts
|

Retention and Leaching of Nutrients in a Limed Ultisol Under Cropping

Abstract: The response of maize (Zea mays L. Cv. TZB) to liming and the retention and leaching of Ca and other nutrient ions were studied in the greenhouse using an acid Ultisol from southern Nigeria. The soil was limed to various pH levels and maize was grown for 10 weeks. The largest growth response occurred when the soil pH was raised from 4.3 to 5.0 by liming (1.3 metric ton/ha). The highest yield was obtained when the soil pH was between 5.5 to 6.0.Substantial downward movement of Ca from the limed surface layer (0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
1
0

Year Published

1979
1979
1994
1994

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 0 publications
2
1
0
Order By: Relevance
“…These findings are in agreement with McLeod and Jackson (1967) who suggested that the concentration of A1 in the soil solution is not directly related to the amount of i cexchangeable A1 in the soil and neither is A1 in the soil solution and soil pH. Reeve and Sumner (1970b) Juo and Ballaux (1977) limed an Ultisol from Nigeria to pH 7.0 and were able to observe severe yield depression at 3 weeks but the condition tended to alleviate itself after 10 weeks. Pearson (1975) suggested that corn yields can be increased by liming when soil pH falls below 5.0 or the A1 saturation exceeds 15%.…”
Section: + Exchangeable A1supporting
confidence: 89%
See 1 more Smart Citation
“…These findings are in agreement with McLeod and Jackson (1967) who suggested that the concentration of A1 in the soil solution is not directly related to the amount of i cexchangeable A1 in the soil and neither is A1 in the soil solution and soil pH. Reeve and Sumner (1970b) Juo and Ballaux (1977) limed an Ultisol from Nigeria to pH 7.0 and were able to observe severe yield depression at 3 weeks but the condition tended to alleviate itself after 10 weeks. Pearson (1975) suggested that corn yields can be increased by liming when soil pH falls below 5.0 or the A1 saturation exceeds 15%.…”
Section: + Exchangeable A1supporting
confidence: 89%
“…), liming at high rates is likely to induce some micronutrient deficiencies, although at the present time it is rather general knowledge that little lime, if any, is needed in most tropical areas for acid-toler-Pennisetum typhoides ) but not tomato plants in an Entisol from Costa Rica when limed at 5 and 10 ton CaCOyha. Reduction in yield was not due to induced Fe deficiency nor were Zn and Cu concentrations in plants below critical levels.Similar results were obtained byJuo and Ballaux (1977) in an Ultisol from Nigeria.Heavy P applications over several years may also significantly reduce levels of available Zn, Cu, and Mn in the soil (Badanur and duced. Similar results in plants were reported by Wallace et al…”
supporting
confidence: 87%
“…al. 1982;Gillman et al 1989;Juo and Ballaux, 1977;Omoti et al 1983;Peason et al 1962;Pleysier and Juo, 1981). Leaching losses varied as a function of the amount of mobile, or leachable, anions present.…”
mentioning
confidence: 99%